TINJAUAN HUKUM ISLAM TERHADAP PENYALURAN ZAKAT MELALUI LEMBAGA AMIL DI INDONESIA - Khairani Harahap, Sarah (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
This article examines the analysis of zakat distribution through amil zakat institutions in Indonesia from the perspective of Islamic law. The phenomenon that occurs is that communities prefer to distribute zakat directly to mustahik, this is influenced by several factors such as religiosity where individuals feel more inner satisfaction if they meet directly with mustahik. This phenomenon needs to be studied how Islamic law views the correct distribution and management of zakat according to sharia. The research purpose is to provide knowledge for readers regarding the law of distributing zakat through amil institutions. This article uses literature research. The data used consists of primary data, namely books that discuss zakat. Second, secondary data in the form of law books and laws. Third, relevant journals. Data collection techniques by analyzing all data then draw conclusions. The result of this research is that zakat must be channeled through an institution so that it can be managed properly. The explicit command of zakat management can be found in verse 103 of Surah at-Taubah. The explanation of Qurtubi's interpretation shows the obligation of zakat to be managed by people who are trusted for it, which in Qurtubi's term is referred to as intermediaries. the need for zakat managers who work to ensure that zakat is received correctly, and especially distributed correctly to the rightful people. The Hadith narrated by Bukhari also emphasizes the importance of zakat management. The word tu'hdzu in the hadith requires zakat to be managed by appointed officials, not paid directly to individuals. So it can be concluded that the distribution of zakat through an amil institution is very mandatory so that zakat management can be managed properly and right on target and in accordance with the objectives of the implementation of zakat.